Revealing the Molecular Signatures of miR-185-5p on Breast Cancer Cells Using Proteomic Analysis - Torun, Vildan; Değerli, Elif; Cansaran-Duman, Demet (Protein and Peptide Letters, 2024)
BackgroundBreast cancer is a heterogeneous type of disease in which genetic and environmental factors play a crucial role. There are several types of treatment for breast cancer (BC) patients. However, the biggest problem in the treatment of breast cancer is the resistance that occurs during the treatment with chemotherapeutic agents. Usnic acid, a secondary metabolite of lichen, has been identified as a drug candidate molecule in cancer treatment. The determination of miRNA target proteins is essential for the understanding of molecular mechanisms of miRNA-related tumorigenesis.ObjectivesWe determined that mir-185-5p has therapeutic potential at the miRNA level by applying usnic acid to BT-474 breast cancer cells in a previous study. Herein, we aimed to investigate the molecular mechanisms of miR-185-5p on BT-474 breast cancer cells using a proteomics approach. We explored the changes in the protein expression level of BT-474 breast cancer cells in response to the up-regulation of miR-185-5p after applying usnic acid as a novel candidate anti-cancer drug molecule.MethodsWe performed quantitative proteome analysis based on an LC-MS/MS assay, which was validated by western blotting. The differentially expressed proteins were analyzed using the latest data available in bioinformatics tools. The up-regulated expression of YWHAE, Cathepsin D, and the down-regulated levels of PAK-1 were demonstrated by western blot assay.ResultsAccording to the results, 86 proteins showing >2-fold change were identified as differentially expressed between breast cancer and normal breast epithelial cells. The apoptosis pathway was the main clade containing most of the proteins regulated by miR-185-5p. The results indicate that miR-185-5p modulates apoptosis signaling pathways in BT-474 breast cancer cells. Breast cancer inhibition due to increased expression of YWHAE, Cathepsin D, and decreased expression of PAK-1 is likely to be mediated by inducing miR-185-5p mediated apoptosis.ConclusionIn this study, the identification of miR-185-5p protein targets demonstrated the potential for the development of targeted therapy and the development of miRNA-based therapeutics and presented it as a biomarker for breast cancer diagnosis, prognosis, and treatment response. In this regard, proteome analyses provided an understanding of the molecular mechanism underlying the effect of miR-185-5p on breast cancer.
Keywords: Breast cancer